2020
DOI: 10.1155/2020/8842651
|View full text |Cite
|
Sign up to set email alerts
|

The Alteration in Composition and Function of Gut Microbiome in Patients with Type 2 Diabetes

Abstract: Background. Diabetes mellitus (DM) has become one of the most common chronic metabolic diseases worldwide. Due to the increasing prevalence and various complications, diabetes brings about a huge financial burden to DM patients. Nowadays, more and more studies reveal the relationship between diseases and gut microbial community. We aimed to explore the alteration in composition and function of the gut microbiome in T2DM patients. Methods. A total of 137 patients with diabetes and 179 age- and gender-matched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…We discovered that compared to DM patients, DR patients had elevated Prevotella, Faecalibacterium, Subdoligranulum, Agathobacteria, and Olsenella and reduced Bacillus, Veillonella, and Pantoea abundances at the genus level (Supplementary Table 3). Moreover, we found that Faecalibacterium and Lachnospira were depleted in DM patients compared with healthy controls at the genus level, and Klebsiella and Enterococcus were enriched (Supplementary Table 4), which was consistent with Zhao's study (Zhao et al, 2020). The results of multiple comparisons between groups at the 0.05 level are marked using lowercase letters (abc), the same letter indicates the difference between the two groups is not significant (p > 0.05), and different letters indicate that the difference between the two groups is significant (p < 0.05).…”
Section: Gut Microbiota Alterations In Patients With Diabetic Retinopathy Diabetes Mellitus Patients Without Diabetic Retinopathy and Consupporting
confidence: 91%
“…We discovered that compared to DM patients, DR patients had elevated Prevotella, Faecalibacterium, Subdoligranulum, Agathobacteria, and Olsenella and reduced Bacillus, Veillonella, and Pantoea abundances at the genus level (Supplementary Table 3). Moreover, we found that Faecalibacterium and Lachnospira were depleted in DM patients compared with healthy controls at the genus level, and Klebsiella and Enterococcus were enriched (Supplementary Table 4), which was consistent with Zhao's study (Zhao et al, 2020). The results of multiple comparisons between groups at the 0.05 level are marked using lowercase letters (abc), the same letter indicates the difference between the two groups is not significant (p > 0.05), and different letters indicate that the difference between the two groups is significant (p < 0.05).…”
Section: Gut Microbiota Alterations In Patients With Diabetic Retinopathy Diabetes Mellitus Patients Without Diabetic Retinopathy and Consupporting
confidence: 91%
“…A previous study found that Enterococcus was positively correlated with obesity (35). Enterococcus was significantly higher in the patients with T2DM in the present study, which is in accordance with a study that showed that Enterococcus was more enriched in the DM group than in the control group (36). Interestingly, the abundance of Enterococcus was higher in both T2DM younger and older age subgroups than in the control younger age subgroup.…”
Section: Discussionsupporting
confidence: 92%
“…72 It has been commonly supported that the genus Bacteroides is significantly decreased in T2DM. 66,73 In line with prior research, our results showed that the SCFA-producing genera were greatly reduced in the db/db mice. Though, in the db/db mice after SG1 treatment, they were enriched obviously, especially the Lachnospiraceae_NK4A136_group, Alistipes, Bacteroides, and Roseburia (Fig.…”
Section: Food and Function Papersupporting
confidence: 91%